La Inteligencia Artificial como utilidad para la Auditoría de Sistemas (2021)
The purpose of this article is to express in a very general way one of the various ways in which Artificial Intelligence serves as a tool to perform a systems audit. In such a way that to carry out this research we chose to make use of a qualitative methodology, reviewing different bibliographic sources and field research in which companies that have developed and implemented artificial intelligence tools to perform a systems audit are analyzed. All this aimed at obtaining new knowledge of the contexts of interest.